2021
DOI: 10.1093/jamia/ocab231
|View full text |Cite
|
Sign up to set email alerts
|

Use of clinical data to augment healthcare worker contact tracing during the COVID-19 pandemic

Abstract: Objective This work examined the secondary use of clinical data from the electronic health record (EHR) for screening our healthcare worker (HCW) population for potential exposures to patients with coronavirus disease 2019. Materials and Methods We conducted a cross-sectional study at a free-standing, quaternary care pediatric hospital comparing first-degree, patient-HCW pairs identified by the hospital’s COVID-19 contact tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Reviewed articles mentioned several limitations of EHR log research ( Supplementary eTable 4 ). Three of the most frequently mentioned limitations echo those observed in the prior review of audit log research 11 : EHR logs do not provide a full view of clinical activity which can involve physical and digital interactions outside the EHR (22 articles), 3 , 26 , 34 , 43 , 55 , 57 , 58 , 61 , 65 , 68 , 73 , 74 , 84–86 , 89 , 91 , 92 , 95 , 103 , 109 , 112 qualitative methods are needed to better understand the context and motivation for observed work (15 articles), 32 , 46 , 53 , 62 , 64 , 68 , 72 , 80 , 85 , 91 , 96 , 97 , 101 , 115 , 118 and logs may not contain enough detail to observe complex workflows (13 articles). 4 , 26 , 32 , 43 , 51 , 56 , 59 , 69 , 75 , 81 , 89 , 90 ,…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Reviewed articles mentioned several limitations of EHR log research ( Supplementary eTable 4 ). Three of the most frequently mentioned limitations echo those observed in the prior review of audit log research 11 : EHR logs do not provide a full view of clinical activity which can involve physical and digital interactions outside the EHR (22 articles), 3 , 26 , 34 , 43 , 55 , 57 , 58 , 61 , 65 , 68 , 73 , 74 , 84–86 , 89 , 91 , 92 , 95 , 103 , 109 , 112 qualitative methods are needed to better understand the context and motivation for observed work (15 articles), 32 , 46 , 53 , 62 , 64 , 68 , 72 , 80 , 85 , 91 , 96 , 97 , 101 , 115 , 118 and logs may not contain enough detail to observe complex workflows (13 articles). 4 , 26 , 32 , 43 , 51 , 56 , 59 , 69 , 75 , 81 , 89 , 90 ,…”
Section: Resultsmentioning
confidence: 93%
“… 78–109 Studies employing vendor- and investigator-derived measures also included different participants ( P < .001). While vendor-measure studies only ever included physicians or advanced practice providers (APPs), a third of investigator-measure studies (34%) included all EHR users who performed the observed activity, 73–76 , 84–90 , 103–108 , 115–118 and another 11% specifically included nurses, medical students, or scribes. 77 , 91–95 , 109 Vendor-measure studies were more likely to include data from multiple institutions (25% vs 8% of studies, P = .025) and to observe overall EHR use, rather than only collect data on a specific activity such as note writing or inbox management (98% vs 48% of studies, P < .001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the median list length of HCP identified through clinical data was significantly larger than conventional processes (82 vs 10). To combat the potential problem of overnotification, which has been noted in other EHR-based exposure investigations, 9 we created a “contact score” that estimated the risk of exposure based on time and type of activity. Our comparison to conventional exposure investigations showed that all HCP who tested positive were above the median of contact scores (Fig.…”
Section: Discussionmentioning
confidence: 99%